2018
DOI: 10.1016/j.neuroscience.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Normal Development of the Perineuronal Net in Humans; In Patients with and without Epilepsy

Abstract: The perineuronal net (PN), a highly organized extracellular matrix structure, is believed to play an important role in synaptic function, including maturation and stabilization. In addition to its role in restricting plasticity, alterations in the PN are implicated in disorders such as epilepsy and schizophrenia. However, the time course of PN development is not known in humans. Therefore we set out to document the developmental timeline of the PN formation in humans in 14 frontal and hippocampal specimens fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 48 publications
1
40
1
Order By: Relevance
“…As prolonged postmortem delay (PMD, or postmortem interval, PMI) between death and tissue collection/fixation has been shown to reduce reactivity for WFA lectin in mice, but not for the major PNN component aggrecan (using pan-aggrecan clone 7D4 [69] ), it has been suggested that early lectin binding site loss due to PMD may lead to discrepancies upon autopsy [42] . A recent report furthermore found clone 7D4 to be uniquely efficacious in staining PNNs in banked postmortem human middle frontal gyrus and hippocampal brain tissue, even among other aggrecan antibodies and where WFA had failed [70] . Therefore, we immunolabeled postmortem cortical tissue from clinically and neuropathologically diagnosed AD and non-demented control brains for ACAN+ PNNs (aggrecan 7D4), dense-core plaques (Thio-S), and microglia (IBA1+) ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…As prolonged postmortem delay (PMD, or postmortem interval, PMI) between death and tissue collection/fixation has been shown to reduce reactivity for WFA lectin in mice, but not for the major PNN component aggrecan (using pan-aggrecan clone 7D4 [69] ), it has been suggested that early lectin binding site loss due to PMD may lead to discrepancies upon autopsy [42] . A recent report furthermore found clone 7D4 to be uniquely efficacious in staining PNNs in banked postmortem human middle frontal gyrus and hippocampal brain tissue, even among other aggrecan antibodies and where WFA had failed [70] . Therefore, we immunolabeled postmortem cortical tissue from clinically and neuropathologically diagnosed AD and non-demented control brains for ACAN+ PNNs (aggrecan 7D4), dense-core plaques (Thio-S), and microglia (IBA1+) ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…PNNs are known to exhibit developmental and regional changes in their cortical expression patterns. Although there are no previous reports of fetal PNN expression, in humans, immature PNNs were first observed in the medial prefrontal cortex at 2 months of postnatal age, reaching mature levels by 8 years 81 . In rats, immature PNNs first develop in layer 6 of the parietal cortex at PND7, an age of brain maturation equivalent to the late gestation human 82 , 83 , followed by more widespread PNN expression in cortical layers 2–6 by PND14, and then adult-like patterns by PND35 84 .…”
Section: Discussionmentioning
confidence: 92%
“…This functional observation combined with our cytoarchitectural findings indicates that the IL PFC is likely one of the last frontal cortical regions to reach maturity. Studies that have examined human post-mortem tissue samples of the frontal cortices and hippocampus have also shown that PV neurons are present from birth, although at low levels, and increase to peak levels at 2 years of age 59 . PNNs begin to form as early as the second month of life but do not reach a mature appearance until around 8 years of age 59 .…”
Section: Discussionmentioning
confidence: 99%